2019
DOI: 10.1016/j.atherosclerosis.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognostic value of coronary flow reserve in psoriasis patients

Abstract: This study analyzed the prognostic role of coronary flow reserve in psoriasis. • 153 psoriatic patients without cardiovascular disease were included. • Coronary microvascular dysfunction was present in 15% of patients. • Coronary flow reserve may be a prognostic marker for events-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Psoriasis is believed to be an independent risk factor for cardiovascular disease [1,3,15], however, the underlying mechanisms are not fully understood. There is evidence that the reduced resistance of the expanded superficial capillary bed is not solely responsible for the massively elevated blood flow in plaque skin.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is believed to be an independent risk factor for cardiovascular disease [1,3,15], however, the underlying mechanisms are not fully understood. There is evidence that the reduced resistance of the expanded superficial capillary bed is not solely responsible for the massively elevated blood flow in plaque skin.…”
Section: Discussionmentioning
confidence: 99%
“…Piaserico et al recently stated that CMD is associated with severe psoriasis, psoriatic arthritis, hypertension, and disease duration greater than 6 years, suggesting that this technique is a reliable prognostic marker for patients with psoriasis without a history of CV events. 42) The perivascular fat attenuation index (FAI) is a recently developed technique that uses computed tomography (CT) to allow physicians to evaluate coronary inflammation using differential mapping of attenuation gradients in pericoronary fat. Elnabawi et al 43) demonstrated a https://doi.org/10.4082/kjfm.20.0053 reduction in the FAI of patients receiving biologic therapy for moderate to severe psoriasis, making this a novel tool to evaluate the effects of psoriasis therapy for coronary artery disease.…”
Section: Imaging In the Evaluation Of Cardiovascular Diseasementioning
confidence: 99%
“…[ 51 ] Piaserico et al showed that CMD was associated with severe psoriasis in 15% of the 153 patients in their study (n=23; OR 3.1, p=0.03). [ 52 ] Similarly, the prevalence of CMD has been assessed in psoriasis patients in a cohort study by Weber et al to quantify myocardial perfusion and myocardial flow reserve (MFR) using positron emission tomography imaging. It was reported that the prevalence of CMD (defined as MFR <2) was 61.3% in patients with psoriatic disease, compared to 38.4% in a matched control population (p=0.004).…”
Section: Psoriasis and Coronary Microvascular Dysfunctionmentioning
confidence: 99%